FREQUENCY OF VITAMIN D DEFICIENCY IN PATIENTS PRESENTING WITH FIBROMYALGIA: Vitamin D Deficiency in Fibromyalgia - Rashid, Samina; Nawaz, Khuram Haq; Fakhr, Amer; Ather, Hammad; Hakeem, Farzana; Yousaf, Rizwan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine frequency of vitamin D deficiency in patients presenting with fibromyalgia and its association with various factors. Study Design: Cross sectional study. Place and Duration of Study: Medicine department, Pak Emirates Military Hospital Rawalpindi, from Sep 2018 to Feb 2019. Methodology: Ninety patients of fibromyalgia were included in the study. Diagnosis of fibromyalgia was made by the consultant rheumatologist on the basis of American College of Rheumatology Criteria needed for fibromyalgia diagnosis and classification. Vitamin D levels <20ng/ml were considered as deficient. Age, education, marital status, menstrual abnormallities and body mass index were correlated with the presence of vitamin D deficiency among the patients suffering from fibromyalgia. Results: Out of 90 patients of fibromyalgia, 57 (63.3%) showed the presence of vitamin D deficiency while 33 (36.7%) had no deficiency of vitamin D. Among the study participants 88 (97.8%) patients were females and only 2 (2.2%) patients were males. Mean age of the patients was 39.4 ± 3.365 years. After applying the binary logistic regression, we found that presence of menstrual abnormalities and high body mass index had significant association with the presence of vitamin D deficiency among the patients of fibromyalgia (p-value<0.05). Conclusion: Vitamin D deficiency emerged as a common finding among the patients of fibromyalgia in a teaching hospital of Pakistan. Vitamin D deficiency should be screened at the rheumatology clinics and special attention should be paid to the patients who are overweight or obese and female patients with the menstrual abnormalities.